Tumor-Related Methylated Cell-Free DNA and Circulating Tumor Cells in Melanoma - Salvianti, Francesca; Orlando, Claudio; Massi, Daniela; De Giorgi, Vincenzo; Grazzini, Marta; Pazzagli, Mario; Pinzani, Pamela (Frontiers in Molecular Biosciences, 2016)
Solid tumor release into the circulation cell-free DNA (cfDNA) and circulating tumor cells (CTCs) which represent promising biomarkers for cancer diagnosis. Circulating tumor DNA may be studied in plasma from cancer patients by detecting tumor specific alterations, such as genetic or epigenetic modifications. Ras association domain family 1 isoform A (RASSF1A) is a tumor suppressor gene silenced by promoter hypermethylation in a variety of human cancers including melanoma. The aim of the present study was to assess the diagnostic performance of a tumor-related methylated cfDNA marker in melanoma patients and to compare this parameter with the presence of CTCs. RASSF1A promoter methylation was quantified in cfDNA by qPCR in a consecutive series of 84 melanoma patients and 68 healthy controls. In a subset of 68 cases, the presence of CTCs was assessed by a filtration method (Isolation by Size of Epithelial Tumor Cells, ISET) as well as by an indirect method based on the detection of tyrosinase mRNA by RT-qPCR. The distribution of RASSF1A methylated cfDNA was investigated in cases and controls and the predictive capability of this parameter was assessed by means of the area under the ROC curve (AUC). The percentage of cases with methylated RASSF1A promoter in cfDNA was significantly higher in each class of melanoma patients (in situ, invasive and metastatic) than in healthy subjects (Pearson chi-squared test, p < 0.001). The concentration of RASSF1A methylated cfDNA in the subjects with a detectable quantity of methylated alleles was significantly higher in melanoma patients than in controls. The biomarker showed a good predictive capability (in terms of AUC) in discriminating between melanoma patients and healthy controls. This epigenetic marker associated to cfDNA did not show a significant correlation with the presence of CTCs, but, when the two parameters are jointly considered, we obtain a higher sensitivity of the detection of positive cases in invasive and metastatic melanomas. Our data suggest that cell-free tumor DNA and CTCs represent two complementary aspects of the liquid biopsy which may improve the diagnosis and the clinical management of melanoma patients.